Manometric and radiologic transcystic examination operative and postoperative in biliary surgery: results and technique - Cendán Alfonzo, Juan E (Cirugía del Uruguay, 1972)
Regardless of the exactness of manometric registers and the obvious limitations resulting from explorations performed under conditions other than the physiological, it can be stated that preoperatory manometric and radiological exploration is a method both necessary and sufficient to guide decision-making with respect to surgery and which limits considerably exploratory choledocotomy, instrumental explorations, etc. When the operating-room lacks roentgentelevision for radiomanometric exploration to follow the course of the perfusion and make dynamics study possible, cholangiography -under manometric control, on the basis of the data obtained in prior studies by means of physiological serum- supplies the necessary information, provided it is performed under adequate conditions, having obtained plates with filling of all the biliary tree, at re.sidual pressure, with thin ]ayer, comprising those images of the duodenal passage which are necessary for a correct interpretation. With this information the data for correcting pathological disturbances can be obtained without adding the istrogenic · factors resulting from instrmental operations, useless cl},oledocotomies, dilatations, indiscriminate or a):msive use of Kehr's drainages, unnecesary papilotom.i es, etc.